Pandemic to endemic: A preparation for technology adaptation - Subrata, Sumarno Adi; Snyder, Keith (Innovation in Health for Society, 2022)
The world reached a point where it was starting to change from a COVID-19 pandemic footing to an endemic area. Although variants of SARS-CoV-2 (novel coronavirus) pend this trajectory, the country may be ready to reimagine its effect on public health systems. Over two years ago, as new variants of COVID-19 emerged, Indonesia's public-health priorities focused on the essential missions of getting society assessed, vaccinated, and boosted while maintaining access to healthcare in hospitals. Inequalities predating the pandemic were laid bare as historically marginalized communities bore the brunt of the pandemic's ill impacts. Many healthcare professionals are now redressing vulnerabilities and planning a more robust path against infection. To help guide them on this journey, the healthcare provider should set forth four imperatives authorities consider when developing a comprehensive strategy to live with COVID-19. As the transition from pandemic to endemic is on the way, defining the next normal, tracking progress, limiting illness and death, and slowing transmission should be performed massively. Governments have a unique role in stewarding evolution by supporting innovative technology to deal with other health issues. The ground on which this next ordinary settle determines whether the lessons during the pandemic are heeded and could create a new habit for public-healthcare systems to emerge more responsive to whatever challenges lie in the future. Finally hope, this pandemic will end soon, and people may generally live without concerns. Keywords: Pandemic; endemic; innovation in health; quality care; health technology